Two birds with one stone: dual grain-boundary and interface passivation enables >22% efficient inverted methylammonium-free perovskite solar cells. Issue 11 (17th August 2021) - Gharibzadeh, Saba; Fassl, Paul; Hossain, Ihteaz M.; Rohrbeck, Pascal; Frericks, Markus; Schmidt, Moritz; Duong, The; Khan, Motiur Rahman; Abzieher, Tobias; Nejand, Bahram Abdollahi; Schackmar, Fabian; Almora, Osbel; et al.
Abstract : We present a dual passivation approach for p–i–n perovskite solar cells using phenethylammonium chloride that simultaneously passivates defects at the grain boundaries and the perovskite/C60 interface, thus substantially enhancing both V OC and FF. Abstract : Advancing inverted (p–i–n) perovskite solar cells (PSCs) is key to further enhance the power conversion efficiency (PCE) and stability of flexible and perovskite-based tandem photovoltaics. Yet, the presence of defects at grain boundaries and in particular interfacial recombination at the perovskite/electron transporting layer interface induce severe non-radiative recombination losses, limiting the open-circuit voltage ( V OC ) and fill factor (FF) of PSCs in this architecture. In this work, we introduce a dual passivation strategy using the long chain alkylammonium salt phenethylammonium chloride (PEACl) both as an additive and for surface treatment to simultaneously passivate the grain boundaries and the perovskite/C60 interface. Using [2-(9 H -carbazol-9-yl)ethyl]phosphonic acid (2PACz) as a hole transporting layer and a methylammonium (MA)-free Cs0.18 FA0.82 PbI3 perovskite absorber with a bandgap of ∼1.57 eV, prolonged charge carrier lifetime and an on average 63 meV enhanced internal quasi-Fermi level splitting are achieved upon dual passivation compared to reference p–i–n PSCs. Thereby, we achieve one of the highest PCEs for p–i–n PSCs of 22.7% (stabilized at 22.3%) by advancing simultaneously the V OC and FF up to 1.162 V and 83.2%, respectively. Using a variety of experimental techniques, we attribute the positive effects to the formation of a heterogeneous 2D Ruddlesden–Popper (PEA)2 (Cs1− x FA x ) n −1 Pb n (I1− y Cl y )3 n +1 phase at the grain boundaries and surface of the perovskite films. At the same time, the activation energy for ion migration is significantly increased, resulting in enhanced stability of the PSCs under light, humidity, and thermal stress. The presented dual passivation strategy highlights the importance of defect management both in the grain boundaries and the surface of the perovskite absorber layer using a proper passivation material to achieve both highly efficient and stable inverted p–i–n PSCs.